Darvyadi Pratisaran against Shitada (Gingivitis) – Case Report. - Sharma, Aparna; Sharma, Ish (International Research Journal of Ayurveda & Yoga, 2023)
Shitada (Gingivitis) is widely detailed in the western Dentistry, as well as in Shalakya Tantra from Ayurveda. It can progress to periodontitis, eventually risking tooth and alveolar bone loss. The prevalence of Shitada (Gingivitis) is significantly high, however underreported. Chronicity warrants long term and repetitive medication with anti inflammatory, and antibiotic agents, paving risks for adverse drug reactions. Pratisarana, the Ayurvedic local management as observed in this single case study offers safe, effective, and economical alternative. This can be extended to the high-risk groups for prevention, and to the patients for management / cure.